APPLICATION OF INDUSTRY 5.0 IN FINANCIAL SECTOR - Swati, Kunwar; Brijesh, Kumar (INTI International University, 2023)
Technology, along with politics and economics, is a major element shaping banking. Technological trends are crucial for banking management make smart decisions, properly anticipate the future, and seize opportunities. The pandemic's aftereffects are available to everyone, and the global economy is currently experiencing a recession. All organizations are susceptible to their unprecedented effects, and the banking sector is no exception. Given the numerous significant shifts and crises in the banking industry, it is crucial to implement creative approaches. The level of management and control of finances, which are the foundation of any country's economy and economic activity. Customers must receive timely, appropriate goods and services from banks and other financial institutions. For banking, a new perspective is needed. Fostering advanced technologies and the digital economy is the next area that needs to be given top priority. Banking 5.0 refers to these changes in light of digital transformation. Edge computing, digital twins, COBOTs, IoT, big data analytics, 6G, and more can help banks cut costs. Products and services costs, retain customers, protect security and privacy, improve risk management, provide error-free financial services and data-driven decision making. Industry 5.0 might focus on hyper-personalization, using AI and data analytics to provide customized financial products and services to individual customers. In an Industry 5.0 scenario, there could be a strong focus on using technology to reach underserved populations and improve financial inclusion, such as providing digital banking services to remote and marginalized communities. It is anticipated that this exploratory study will lay the foundation for later research that will empirically examine the adoption of I5.0 technologies within banks.